Build your own transistor radios : a hobbyist's guide to high-performance and low-powered radio circuits - Quan, Ronald (Build Your Own., 2013)
A DIY guide to designing and building transistor radios Create sophisticated transistor radios that are inexpensive yet highly efficient. Build Your Own Transistor Radios: A Hobbyist's Guide to High-Performance and Low-Powered Radio Circuits offers complete projects with detailed schematics and insights on how the radios were designed. Learn how to choose components, construct the different types of radios, and troubleshoot your work. Digging deeper, this practical resource shows you how to engineer innovative devices by experimenting with and radically improving existing designs. Build You.